MIL-101(Cr) for CO2 Conversion into Cyclic Carbonates, Under Solvent and Co-Catalyst Free Mild Reaction Conditions; Catalysts; Vol. 10, iss. 4 - Akimana E. Emmanuelia; Wang J. Jichao; Likhanova N. V. Nataljya Vladimirovna; Chaemchuen Somboon; Verpoort F. V. K. Frensis Valter Kornelius (2020, 2020)
Title screen